Dermatofibroma associated with a sweat duct skin cyst - Jan Hrudka; Jakub Kníže; Kateřina Bodianová (Elsevier, 2022)
Dermatofibroma or fibrous histiocytoma is a very common benign mesenchymal skin tumor that usually involves lower limbs and shows slight predilection for young females. There are several histological subtypes with variable biological significance in terms of local recurrence risk. Herein, we present an interesting case of a middle-aged man presenting with a voluminous cystic skin tumor on the left shin which on histopathologic examination revealed a dermatofibroma associated with a large cyst lined with non-keratinizing squamous epithelium admixed with sweat gland-type glandular epithelial cells. There are two references describing similar cases in the literature.